Bioceramic coatings for medical implants : trends and techniques - Heimann, R. B. (Robert Bertram), 1938-; Lehmann, Hans D. (Wiley-VCH., 2015)
Reflecting the progress in recent years, this book provides in-depth information on the preparation, chemistry, and engineering of bioceramic coatings for medical implants. It is authored by two renowned experts with over 30 years of experience in industry and academia, who know the potentials and pitfalls of the techniques concerned. Following an introduction to the principles of biocompatibility, they present the structures and properties of various bioceramics from alumina to zirconia. The main part of the work focuses on coating technologies, such as chemical vapor deposition, sol-gel depos.